Diversity and Abundance of Arthropods and Predators of the Fall Armyworm, Spodoptera Frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) in Maize Agroecosystems and their Potential for Biological Control - Idemudia, I. (University of Ghana, 2023)
The fall armyworm, Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) is native to the tropical and subtropical regions of the Americas. It is currently the most devastating invasive arthropod pest of maize in sub-Saharan Africa. Following the first report of S. frugiperda in Ghana in 2016, its control has been reliant on synthetic chemical insecticides. Due to reliance and overuse of these insecticides, the pest has evolved resistance and requires higher application frequencies for control. Furthermore, non-target/beneficial organisms are negatively impacted by insecticides. Therefore, this thesis sought to investigate the role of two different management options of S. frugiperda on the diversity and abundance of arthropod species, including predators as well as the infestation levels of S. frugiperda in maize agroecosystems at the Soil and Irrigation Research Centre (SIREC) of the University of Ghana, Kpong, located within the lower Volta basin of the Coastal Savannah agro-ecological zone of Ghana. The investigations were conducted in the major and minor maize cropping seasons. Also, evaluations of the predatory potential and functional response of the predator Rhynocoris bicolor (Fabricius) were made following the recommendations by the Centre of Agriculture and Bioscience International (CABI) and the Plant Protection and Regulatory Services Directorate (PPRSD) of the Ministry of Food and Agriculture (MoFA). The field experiment consisted of two different treatment plots: a biocontrol maize plot (BCM) where augmentative releases of the egg parasitoid, Telenomus remus (Nixon) were made and maize plot with farmer’s practice (MFP) in which the insecticide; Emamectin benzoate-based product, Ataka Super EC®: Emamectin benzoate 19.2 g/l was applied. A control maize plot without any treatment was included. The predatory potential of the predator R. bicolor was determined in laboratory assays at the PPRSD biocontrol laboratory in Pokuase, Accra. Results showed that both in the major and minor maize cropping seasons, significantly more arthropods, including predators were recorded in the control plots than in the MFP plots. Further, the diversity of the arthropods including predators was significantly lower in the MFP plot than in the control and BCM plots, articulating that the insecticides used by maize growers in Ghana had adverse effects on the arthropod communities and reduce biocontrol services. Conversely, a total of seven predatory arthropods: Crematogaster striatula (Emery), Cosmolestes pictus (Klug), Haematochares obscuripennis (Stal), Hediocoris tibialis (Stal), Rhynocoris sp. Sphedanolestes picturellus (Schouteden), and Misumenops sp. were confirmed predators of S. frugiperda after laboratory tests. The laboratory assays on R. bicolor revealed that the predator exhibits a type II functional response, with S. frugiperda as prey. Hence, could be considered a potential biocontrol agent of S. frugiperda in Ghana.
MPhil. Entomology
Keywords: armyworm; Ghana; sub-Saharan Africa; Soil and Irrigation Research Centre (SIREC)